EKSPERIMENTASI METODE PEMBELAJARAN BRAINSTORMING TERHADAP PRESTASI BELAJAR RISET OPERASI POKOK BAHASAN PROGRAM LINEAR - Abdul Azis (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Based on data released by the Program for International Student Assessment (PISA) in early December of 2013 shows the mathematical ability of students in Indonesia ranked 64 out of 65 countries. In addition, according to Third In International Mathematics Science and Studies (TIMSS) Year 2011 shows the rank of Indonesian children are in position 38 of 42 countries.Operations Research with the subject of the Linear Program is one of the most closely related courses of mathematics. After observation during the learning process, most students have not really understood well the concept of this material and how its application in real life.Application of learning combined with the use of tools in the form of technology (software) will greatly help students to be able to understand the concept of the material as a whole, because basically the development of technology-based learning method is made in accordance with the original concept and displayed in an easy to understand.Graphmatica is a graphical software maker created by k.soft, Inc. Graphmatica software has advantages in knowing the position (position) of an image of an equation or linear inequality, quadratic function, etc. With the application of Graphmatica software will be able to increase spatial quotient, which is spatial quotient is one of multiple intelligences that focus more on the ability of analyzing the image or space and subject matter Linear Program is one of the materials that prioritize the analysis of images or graphics. Based on the description above, in this research will use Brainstorming method based on Graphmatica Software.The purpose of this study is to produce learning tools as implementation of Brainstorming method based onGraphmatica Software through research and development (Research and Development). The expected outputof this research is the Linear Programs textbook and Brainstorming method with Graphmatica Software. Keywords: Brainstorming, Spatial Quotient, Graphmatica